2013
DOI: 10.5614/j.eng.technol.sci.2013.45.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady Aerodynamics of Flapping Wing of a Bird

Abstract: The unsteady flow behavior and time characteristics of the flapping motion of a bird computational method. During wing surfaces and surrounding flow flow changes in the flow of flapping speed on unsteady aerodynamic load, two kinds of computational simulations were carried out, namely To mimic the movement of flapping path accorded dihedral angle and time. The computations of time based on the solution of applying the k-ε turbulen computational domain around the model use provide more accuracy wing and body su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
2
1
0
Order By: Relevance
“…It reduces for higher α with higher wind speeds. Similar to the findings of Bie et al (40) , Chang et al (47) and Moelyadi et al (41) , low pressure on the upper surfaces of the wing in flight increases lift with accompanying drag. In general, increasing the angle-of-attack significantly increases lift.…”
Section: Case 3: Wrist Joint and The Effects Of Varying Wing Twistsupporting
confidence: 83%
See 2 more Smart Citations
“…It reduces for higher α with higher wind speeds. Similar to the findings of Bie et al (40) , Chang et al (47) and Moelyadi et al (41) , low pressure on the upper surfaces of the wing in flight increases lift with accompanying drag. In general, increasing the angle-of-attack significantly increases lift.…”
Section: Case 3: Wrist Joint and The Effects Of Varying Wing Twistsupporting
confidence: 83%
“…The higher flapping frequency (2.5Hz) performs better than the lower frequency (1.5Hz). Moelyadi et al (41) performed flow simulations on a seagull-inspired wing under pure flapping motion and showed that the wing would be aerodynamically efficient and stable at flapping frequency of 3Hz, close to the highest and optimal frequency investigated in the present study (i.e. 2.5Hz).…”
Section: Case 1: Shoulder Joint and The Effects Of Varying The Flapping Amplitude Flapping Frequency And Stroke Ratiosupporting
confidence: 73%
See 1 more Smart Citation